Social Media’s Impact on Sustainability Engagement: Brands, NGOs, and Influencers - Harliyono, Maria; Priskila (Jogjakarta Communication Conference (JCC), 2025)
As social media becomes a dominant channel for advocacy and marketing, its role in promoting sustainability is increasingly vital. This study examines how brands, non-governmental organizations (NGOs), and influencers utilize social media platforms—Instagram, TikTok, and X (formerly Twitter)—to engage audiences in sustainability campaigns. By conducting a comparative content analysis of 30 accounts (10 per category), this research identifies key persuasive strategies, engagement levels, and audience sentiment toward sustainability messaging. Preliminary findings suggest that influencers generate higher engagement and trust among audiences, while NGOs are perceived as the most credible sources of sustainability advocacy. Brands, despite their extensive reach, often face skepticism due to concerns over greenwashing. Posts that incorporate emotional storytelling and direct calls to action tend to receive higher engagement compared to purely informational content. Additionally, visual content such as short-form videos on TikTok and Instagram Reels attracts significantly more audience interaction than text-based posts on X.By analyzing these dynamics, this study provides insights into the effectiveness of digital sustainability campaigns and offers recommendations for optimizing social media strategies to enhance public participation in sustainability efforts. The findings will support organizations, policymakers, and content creators in developing more impactful sustainability messaging in the digital era.